Messengers of sex : hormones, biomedicine, and feminism - Roberts, Celia, 1968- (Cambridge studies in society and the life sciences., 2007)
Since the early 20th century, hormones have commonly been understood as 'messengers of sex'. They are seen as essential to the development & functioning of healthy reproductive male & female bodies. In this book, Celia Roberts analyses the multiple ways in which sex hormones have come to matter to us today.